2013
DOI: 10.1016/j.bcp.2013.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of the alpha-7 nicotinic acetylcholine receptor in the pathophysiology and treatment of schizophrenia

Abstract: The group of schizophrenia disorders affects approximately 1% of the population and has both genetic and environmental etiologies. Sufferers report various behavioral abnormalities including hallucinations and delusions (positive symptoms), reduced joy and amotivation (negative symptoms), plus inattention and poor learning (cognitive deficits). Despite the heterogeneous symptoms experienced, most patients smoke. The self-medication hypothesis posits that patients smoke to alleviate symptoms, consistent with ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 194 publications
(225 reference statements)
2
94
0
Order By: Relevance
“…Accumulating evidence indicate that alpha-7 nicotinic acetylcholine receptor, which has a significant effect on cognitive processes, plays an important role in the pathophysiology of schizophrenia and previous studies demonstrated that alpha-7 nicotinic acetylcholine agonists had emerged as a potential treatment target for the treatment of CIAS (Freedman, 2014;Nikiforuk, Kos, Potasiewicz, & Popik, 2015;Young & Geyer, 2013). PHA-543613, an alpha-7 nicotinic partial agonist, has been reported to improve MWM performance in Aβ 25-35 -induced cognitive deficits mice (Sadigh-Eteghad et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicate that alpha-7 nicotinic acetylcholine receptor, which has a significant effect on cognitive processes, plays an important role in the pathophysiology of schizophrenia and previous studies demonstrated that alpha-7 nicotinic acetylcholine agonists had emerged as a potential treatment target for the treatment of CIAS (Freedman, 2014;Nikiforuk, Kos, Potasiewicz, & Popik, 2015;Young & Geyer, 2013). PHA-543613, an alpha-7 nicotinic partial agonist, has been reported to improve MWM performance in Aβ 25-35 -induced cognitive deficits mice (Sadigh-Eteghad et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Freedman et al [11] have suggested a link between impaired auditory sensory gating and α7 NAChR gene single-nucleotide polymorphism on the promoter regions of chromosome 15q14 locus. Furthermore, postmortem studies demonstrated that α7 NAChR binding levels and protein expressions decreased in dentate gyrus, hippocampal CA3 region, cingulate cortex, and prefrontal cortex, which are important regions for modulating cognitive function [12][13][14]. In addition to this, the fact that the prevalence of tobacco consumption of schizophrenia patients is higher compared with healthy individuals encourages researchers to examine nicotinic receptors in schizophrenia pathogenesis and treatment [15].…”
Section: Introductionmentioning
confidence: 99%
“…Possibly reflecting single nucleotide changes within promoter regions of CHRNA7 (Leonard et al 2002), diminished numbers of apparently structurally intact α7 nAChRs have been shown in the hippocampus (Freedman et al 1995), frontal cortex (Guan et al 1999) and the nucleus reticularis thalami (Court et al 1999) of SZ postmortem brains. Results from clinical trials of novel α7 molecules in SZ patients have been mixed (Young and Geyer 2013). DMXB-A (a.k.a.…”
Section: Introductionmentioning
confidence: 99%